Deep Down - Ballantyne, R. M. (Saga Egmont, 2022)
Young Dr. Oliver Trembath has arrived in the small mining town of St. Just, in Cornwall, where he learns about the tin and copper mines of the area and meets those who have worked them for generations. Romance and adventure ensues in this charming and informative historical adventure tale by popular author R.M. Ballantyne.